Evaluation of teratogenic effects of crocin and safranal, active ingredients of saffron, in mice. (February 2016) - Moallem, Seyed Adel; Afshar, Mohammad; Etemad, Leila; Razavi, Bibi Marjan; Hosseinzadeh, Hossein
Saffron ( Crocus sativus ) is a widely used food additive for its color and taste. Crocin and safranal are two main components of this plant. Numerous studies are underway to introduce saffron and its active ingredients as pharmacological agents. Safety assessments of these compounds are important parts of this endeavor. In this study, the effects of crocin and safranal administrations during embryogenesis have been investigated in mice. A total of 75 BALB/c pregnant mice were divided into six experimental and control groups. Four experimental groups received intraperitoneal injection of crocin (200 mg/kg or 600 mg/kg) daily or safranal (0.075 ml/kg or 0.225 ml/kg) on gestational days (GDs) 6 to 15. Control groups received normal saline or paraffin as solvents of crocin and safranal. Dams were dissected on GD18 and embryos were collected. Routine maternal and fetal parameters were recorded. Macroscopic observation of external malformations was also performed. Fetuses were then selected for double skeletal staining with alizarin red and alcian blue. All experimental groups caused significant decrease in length and weight of fetuses when compared with the control groups and revealed malformations such as minor skeletal malformations, mandible and calvaria malformations, and growth retardation. Minor skeletal malformations were the most commonly observed abnormality, which were statistically significant when compared with the control groups ( p  < 0.05). The severities of malformations were comparable in the crocin- and safranal-treated groups. This study suggests that crocin or safranal can induce embryonic malformations when administered in pregnant mice. Due to the wide use of saffron, further elaborate studies to understand the malformation mechanisms of these ingredients are recommended.